Pregnancy outcomes in patients with kidney transplant-A retrospective snapshot - Chaudhary, Aghosh-e-Gul; Gulzar, Hina; Qayyum, Ahad (Pakistan Journal of Kidney Diseases, 2024)
Pregnancy in renal transplantation is a sensitive issue since fertility improves shortly after transplantation and the prevalence of pregnancy-related complications in these patients are more in comparison to non-transplanted matched cohorts. Our study aimed at assessing the outcomes of pregnancy in our transplant patients. Methods: This study was designed as a questionnaire based retrospective cross-sectional study wherein the authors contacted all their patients who underwent kidney transplantation under our care and now being followed with us or 4 other hospitals. Results: Total of 20 females conceived unplanned, out of 130 females of child bearing age who underwent kidney transplant. single pregnancy ended up in elective abortion at 4th month after transplant, rest of the pregnancies were successful and uneventful. Conclusion: Fertility related issues should be included in the counselling of kidney transplant females for planned pregnancy. Successful outcome is quite possible. There is a critical need for comprehensive support systems, including counseling, education, and resources, to empower female kidney transplant recipients in their reproductive journeys and to address the gaps in understanding family planning and contraceptive methods in the post-transplant period.